Building energy metering - Salazar, Ellen (TM (Chartered Institution of Building Services Engineers) ;, 2009)
This document promotes best practice in the design of energy metering and submetering (not smart metering) in non-domestic buildings. It will also help facilities managers to introduce metering and submetering in their existing buildings. To this end, it has been written for designers, owner-occupiers, landlords and the letting agents who act on their behalf, managing agents, tenants, office managers, facilities managers, and anyone else who can benefit from the energy data that meters and submeters can provide. This edition of TM39 offers a cost-effective and practical approach to procuring energy metering systems. It should be used to optimise the metering strategy against cost, practicality, the value of the information gained and future energy savings. A step-by-step method is provided to assist in the selection of appropriate ways of metering energy use and the provision of information, including provision of a logbook, for building owners and occupiers. --